Cover Feature: Site‐Selective C–H Amidation of 2‐Aryl Quinazolinones Using Nitrene Surrogates (Eur. J. Org. Chem. 46/2020). Issue 46 (6th November 2020) - Kim, Saegun; Jeoung, Daeun; Kim, Kunyoung; Lee, Seok Beom; Lee, Suk Hun; Park, Min Seo; Ghosh, Prithwish; Mishra, Neeraj Kumar; Hong, Suckchang; Kim, In Su
Abstract : The Cover Feature shows the rhodium(III) and iridium(III)‐catalyzed C–H amidation reaction of 2‐aryl quinazolin‐4(3 H )‐ones with a range of nitrene surrogates including dioxazolones dioxazolones, organic azides, and N ‐methoxyamides through N ‐assisted C–H activation. Complete site‐selectivity and functional group tolerance are observed. Notably, the large‐scale reaction and late‐stage functionalization highlight the synthetic potential of the developed protocol. This work is dedicated to Prof. Pierre H. Dixneuf for his outstanding contribution to organometallic chemistry and catalysis. More information can be found in the Full Paper by S. Hong, I. S. Kim et al.